Analisis Pendekatan Sistem: Optimalisasi Hasil Belajar - Riska khairani siregar; Suci Nurhayati; Maulana Hakim (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
The systems approach in education aims to improve the quality of student learning outcomes by integrating various interrelated components in the learning process. This article discusses the concept and implementation of a systems approach to optimize learning outcomes in educational environments. This approach views education as a system consisting of various elements, such as curriculum, teaching, students, facilities, and evaluation that interact and influence each other. With this approach, each element in the system is expected to function optimally to achieve the desired educational goals. This study identifies how these elements work together to improve the quality of learning outcomes, including external factors such as motivation, learning styles, and the use of technology in learning. The application of the systems approach focuses on creating a learning environment that supports and enables students to develop their potential optimally. In this study, it was found that by adopting a systems approach, learning management can be more focused and coordinated, thereby increasing the effectiveness and efficiency of learning. In addition, the use of learning strategies that are appropriate to student characteristics also contributes to the achievement of better learning outcomes. These findings are expected to be the basis for the development of more effective and systems-based learning models in order to face future educational challenges.